The Oxford handbook of management theorists - Witzel, Morgen; Warner, Malcolm (Oxford : Oxford University Press, 2013)
The handbook will evaluate the ideas and influence of 25 major management theorists, examining their impact on the evolvement of management as a discipline. The chapters will review the contributions of these theorists in light of their contemporary context and each other, from the pioneers to post-war theorists and later business school theorists.
Includes bibliographical references and index.
Keywords: Management -- History; Management -- Philosophy; Leadership